Co‐Reactant and Annihilation Electrogenerated Chemiluminescence of [Ir(df‐ppy)2(ptb)]+ Derivatives. Issue 8 (3rd March 2020) - Soulsby, Lachlan C.; Agugiaro, Johnny; Wilson, David J. D.; Hayne, David J.; Doeven, Egan H.; Chen, Lifen; Pham, Tien T.; Connell, Timothy U.; Driscoll, Aaron J.; Henderson, Luke C.; Francis, Paul S.
Abstract: The [Ir(df‐ppy)2 (ptb)] + complex (where df‐ppy=2‐(2, 4‐difluorophenyl)pyridine anion; ptb=1‐benzyl‐1, 2, 3‐triazol‐4‐ylpyridine) has previously been shown to be a promising blue luminophore for electrogenerated chemiluminescence (ECL). Herein, we examine the ECL of three [Ir(df‐ppy)2 (ptb)] + derivatives (containing df(CF3 )‐ppy‐Me, df(CN)‐ppy, or df‐ppy‐CF3 ligands) in comparison with the parent complex. In the annihilation mode, all four complexes exhibited ECL, although the emission from [Ir(df(CN)‐ppy)2 (ptb)] + was weak and red‐shifted from its photoluminescence. The absence of this shift in the corresponding reductive‐oxidation co‐reactant ECL with benzoyl peroxide (BPO), and the very low ECL intensity in oxidative–reductive co‐reactant ECL with tri‐ n ‐propylamine (TPrA) enables this effect to be ascribed to oxidative degradation. The [Ir(df‐ppy‐CF3 )2 (ptb)] + complex gave the greatest ECL intensities of the four [Ir ( C ∧ N ) 2 (ptb)] + complexes in the annihilation mode and through both co‐reactant pathways, and shows great potential as a blue electrochemiluminophore. In "mixed annihilation" ECL experiments involving the oxidation of Ir(ppy)3 and the reduction of the [Ir ( C ∧ N ) 2 (ptb)] + complexes, only [Ir(df‐ppy)2 (ptb)] + and [Ir(df(CF3 )‐ppy‐Me)2 (ptb)] + elicited the green ECL from Ir(ppy)3 *, as the electron‐withdrawing substituents on the other two complexes lower the SOMO energy of the reduced complexes below that required to attain the Ir(ppy)3 * excited state upon reaction with [Ir(ppy)3 ] + . Abstract : Feeling blue : The influence of electron‐withdrawing/donating substituents on the electrogenerated chemiluminescence (ECL) of a benchmark blue luminophore [Ir(df‐ppy)2 (ptb)] + (where df‐ppy=2‐(2, 4‐difluorophenyl)‐pyridine anion; ptb=1‐benzyl‐1, 2, 3‐triazol‐4‐ylpyridine) is explored, providing new insight into the ECL of iridium complexes, and revealing a trifluoromethyl derivative as a superior blue electrochemiluminophore.